A multicentre, prospective, randomized, controlled study to evaluate the use of a fibrin sealant as an adjunct to sutured dural repair*. (2nd January 2015) - Green, Alexander L.; Arnaud, Axel; Batiller, Jonathan; Eljamel, Sam; Gauld, Judi; Jones, Peter; Martin, Didier; Mehdorn, Maximilian; Ohman, Juha; Weyns, Frank
Abstract: Background. Obtaining intra-operative watertight closure of the dura is considered important in reducing post-operative cerebrospinal fluid (CSF) leak. The purpose of this study was to evaluate a fibrin sealant as an adjunct to sutured dural repair to obtain intra-operative watertight closure in cranial neurosurgery. Methods. This randomized, controlled multicenter study compared a fibrin sealant (EVICEL ® Fibrin Sealant [Human]) to sutured dural closure (Control). Subjects underwent supratentorial or posterior fossa procedures. Following primary dural repair by sutures, the closure was evaluated for intra-operative CSF leak by moderately increasing the intracranial pressure. If present, subjects were randomized to EVICEL ® or additional sutures (2:1 ratio), stratified by surgical approach. Following treatment, subjects were successful if no CSF leaks were present during provocative challenge. Safety was assessed to 30 days post-surgery, including incidence of CSF leakage. Results. One hundred and thirty-nine subjects were randomized: 89 to EVICEL ® and 50 to Control. Intra-operative watertight closure was achieved in 92.1% EVICEL ® -treated subjects versus 38.0% controls; a treatment difference of 54.1% ( p < 0.001). The treatment differences in the supratentorial and posterior fossa strata were 49.1% and 75.7%, respectively ( p < 0.001). The incidence of adverse events was similar between treatment groups. No deaths or unexpected serious adverse drug reactions were reported. CSF leakage within 30 days post-operatively was 2.2% and 2.0% in EVICEL ® and control groups, respectively. In addition, 2 cases of CSF rhinorrhoea were observed in the EVICEL ® group. Although not associated with the suture line where EVICEL ® was applied, when combined with the other CSF leaks, the observed leak rate in the EVICEL ® group was 4.5%. Conclusions. These results indicate that EVICEL ® is effective as an adjunct to dural sutures to provide watertight closure of the dura mater in cranial surgery. The study confirmed the safety profile of EVICEL ® .